Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1745-7254.2007.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of PSD-95 for dopamine D1receptor modulating glutamate NR1a/NR2B receptor function

Abstract: The present study provides the first evidence that PSD-95 is essential in D1R-regulated NR1a/NR2B receptor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
(27 reference statements)
4
19
0
Order By: Relevance
“…It may be suggested that the inhibition induced by Hal or the Cloz D 2 R blockade is the result of the inhibitory effect on the PFC NMDAR; subsequently, the inhibition would deteriorate the therapeutic effect, based on the DA function imbalance hypothesis [1,2] . As to the indirect interaction between SPD and NMDAR, we obtained definite evidence requiring postsynaptic density-95 (PSD-95) [21] . In an in vitro study, when PSD-95 was co-expressed with D 1 R and NMDAR in HEK293 cells, the activation of D 1 R could enhance NMDAR-mediated Ca 2+ influx [21] .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It may be suggested that the inhibition induced by Hal or the Cloz D 2 R blockade is the result of the inhibitory effect on the PFC NMDAR; subsequently, the inhibition would deteriorate the therapeutic effect, based on the DA function imbalance hypothesis [1,2] . As to the indirect interaction between SPD and NMDAR, we obtained definite evidence requiring postsynaptic density-95 (PSD-95) [21] . In an in vitro study, when PSD-95 was co-expressed with D 1 R and NMDAR in HEK293 cells, the activation of D 1 R could enhance NMDAR-mediated Ca 2+ influx [21] .…”
Section: Discussionmentioning
confidence: 85%
“…As to the indirect interaction between SPD and NMDAR, we obtained definite evidence requiring postsynaptic density-95 (PSD-95) [21] . In an in vitro study, when PSD-95 was co-expressed with D 1 R and NMDAR in HEK293 cells, the activation of D 1 R could enhance NMDAR-mediated Ca 2+ influx [21] . SPD hence could not display its enhancing effect on NMDAR under such experimental conditions without PSD-95.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, dopamine increases NMDAR-mediated calcium influx in a PSD-95-dependent manner, 238 further supporting the role of PSD-95 as a scaffold linking various signaling pathways. In the nucleus accumbens, the dopamineinduced increase in NMDAR-mediated calcium influx is mediated by PKA and PKC and can be reversed by activity of the pathway of dopamine-and cAMP-regulated phosphoprotein (DARPP-32; M r 32 kD) and PP-1, 239 indicating that the effect of dopamine is mediated through phosphorylation.…”
Section: Modulation Of Nmda Receptors By Other Receptorsmentioning
confidence: 92%